Damage response of steel plate to underwater explosion: Effect of shaped charge liner. (May 2017) - Zhang, Zhifan; Wang, Longkan; Silberschmidt, Vadim V.
Abstract: A shape of charge liners has a great effect on formation of a metal jet and its penetration into a target. In this paper, three different shapes of a charge liner, namely, conical, hemispherical and spherical-segment, are chosen to investigate their effect on damage response of a plate to underwater explosion. A Smooth Particle Hydrodynamic (SPH) method based on mesh-free Lagrange formulation is applied to simulate an entire process of a shaped-charge detonation, formation of a metal jet as well as penetration on a steel plate. Initially, a SPH model of the shaped charge with a spherical-segment liner is developed, and its results are compared with experimental data to verify the effectiveness of this method. Then, numerical simulations of shaped charges with different liners are performed to study the damage characteristics of a steel plate subjected to underwater-explosion shock loading and the metal jet. It was found that for the shock wave the peak value of the radial pressure is larger than that of the axial pressure during the detonation process; the level of pressure in the spherical-segment case was higher than that of the other two cases. After the detonation, the metal jet was gradually produced under the effect of the detonation wave. Three types of the metal jet - a shaped charge jet (SCJ), a jetting projectile charge (JPC) and an explosive formed projectile (EFP) – were formed corresponding to three cases with conical, hemispherical and spherical-segment liners. The obtained results show that the velocity and length of the SCJ in the conical case are greater than that of the other cases, and it therefore may lead to a larger penetration depth. In addition, the EFP has a better motion stability for a velocity difference in the spherical case is lower than that of the other two cases. Subsequently, the shock wave arrives at the plate earlier than the metal jet, which will cause deformation of the plate. Due to higher pressure, the shock wave in the spherical-segment case has a stronger damaging effect on the plate than that in the other two cases. Finally, the metal jet reaches the plate causing a hole. Because of a wider jet head, the EFP results in a more serious damage to the plate. The suggested analysis and its results provide a reference for structural design of shaped charge warheads.